2009
DOI: 10.1016/j.juro.2009.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Double-Cross Flap Protection: New Technique for Coverage of Neourethra in Hypospadias Repair

Abstract: Double-cross flap protection is safe and significantly reduces the incidence of postoperative fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
27
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…[14] The aetiology of fistulas and wound dehiscence has formation in hypospadias surgery is the introduction of a protective intermediate layer between the neourethra and the skin. [12][13][14] A well-vascularised adjacent tissue, such as a dartos flap, significantly decreases fistula formation. [2,3,6,[8][9][10][11][12][13][14] Several operative procedures have been reported in literature to decrease the incidence of the complications.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…[14] The aetiology of fistulas and wound dehiscence has formation in hypospadias surgery is the introduction of a protective intermediate layer between the neourethra and the skin. [12][13][14] A well-vascularised adjacent tissue, such as a dartos flap, significantly decreases fistula formation. [2,3,6,[8][9][10][11][12][13][14] Several operative procedures have been reported in literature to decrease the incidence of the complications.…”
Section: Discussionmentioning
confidence: 99%
“…[12][13][14] A well-vascularised adjacent tissue, such as a dartos flap, significantly decreases fistula formation. [2,3,6,[8][9][10][11][12][13][14] Several operative procedures have been reported in literature to decrease the incidence of the complications. [9][10][11][12][13][14][15][16][17][18][19] Authors have reported the use of dorsal subcutaneous preputial flaps, ventral subcutaneous flaps, dartos flaps, external spermatic fascia flaps, spongioplasty, tunica vaginalis and scrotal dartos flaps.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations